SUBTITLING STRATEGIES IN OMETV: A CASE STUDY OF INDAH ASMIGIANTI - Nurul Huda Ahmad Hasibuan (LINGUISTIK TERAPAN, 2023)
Subtitling strategies used by subtitlers in transferring the message of speaker’s utterances from one language to another language in the audiovisual landscape. The purpose of this study is to explain the reasons for employing subtitling strategies in the subtitle of Indah Asmigianti on OmeTV. It adopted a descriptive qualitative method. The study focuses on understanding the reasons behind the utilization of subtitling strategies in the subtitles of Indah Asmigianti's YouTube channel. The data were taken from utterances of Indah Amigianti and four strangers. The source of data was taken from Indah Asmigianti’s YouTube channel which was uploaded on January 02, 2023, with the title “Korean People Got Shocked When I Spoke Their Language” complete with its subtitle. The analysis of subtitling strategies in Indah Asmigianti's conversations based on Dries's theory (1995), reveals that there were two main reasons behind the use of subtitles, namely traditions and the strategies accustomed for both the source and target viewers. Notably, historical circumstances did not emerge as a significant factor in this particular research. An intriguing discovery in this study was the influence of localization in the subtitling process. This newfound insight contributes to a deeper understanding of subtitling complexities, particularly as a form of cultural translation in the digital landscape.